2018
DOI: 10.1016/j.bbadis.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

SURF1 knockout cloned pigs: Early onset of a severe lethal phenotype

Abstract: Leigh syndrome (LS) associated with cytochrome c oxidase (COX) deficiency is an early onset, fatal mitochondrial encephalopathy, leading to multiple neurological failure and eventually death, usually in the first decade of life. Mutations in SURF1, a nuclear gene encoding a mitochondrial protein involved in COX assembly, are among the most common causes of LS. LSSURF1 patients display severe, isolated COX deficiency in all tissues, including cultured fibroblasts and skeletal muscle. Recombinant, constitutive S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
4
15
0
1
Order By: Relevance
“…Shreds of evidence suggest that SURF1 mutations lead to metabolic impairments in neural progenitor cells (NPCs), which cannot switch from glycolytic to OXPHOS metabolism, with subsequent aberrant proliferation and insufficient support for neuronal morphogenesis [ 416 ]. A similar neuronal impairment was reported in a SURF1 ko pig model [ 417 ]. Cerebral organoids from LS patients carrying MT-ATP6 mutations also showed defective corticogenesis and suggest pre-natal impairment [ 418 ].…”
Section: Future Perspectivessupporting
confidence: 84%
“…Shreds of evidence suggest that SURF1 mutations lead to metabolic impairments in neural progenitor cells (NPCs), which cannot switch from glycolytic to OXPHOS metabolism, with subsequent aberrant proliferation and insufficient support for neuronal morphogenesis [ 416 ]. A similar neuronal impairment was reported in a SURF1 ko pig model [ 417 ]. Cerebral organoids from LS patients carrying MT-ATP6 mutations also showed defective corticogenesis and suggest pre-natal impairment [ 418 ].…”
Section: Future Perspectivessupporting
confidence: 84%
“…Microcephaly has often been reported in LS patients 2 . SURF1 knock-out piglets, while not fully recapitulating the clinical phenotype of LS SURF1 , also exhibited developmental alterations and reduced cortical thickness 18 . Moreover, a mutation in the mtDNA gene MT-ATP6 that is associated with LS 39 also caused abnormal NPC functionality 31 .…”
Section: Discussionmentioning
confidence: 93%
“…However, the mechanistic and pathophysiological understanding of LS SURF1 is hindered by the lack of effective model systems. SURF1 knock-out has been carried out in several animals (flies, mice, zebrafish, and piglets) but all these efforts failed to fully recapitulate the neurological phenotypes of human LS SURF1 [14][15][16][17][18] . Here, we report the generation of a human mechanistic model of LS SURF1 based on patient-derived 2D neural cultures and 3D brain organoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriately it was reported that in a cohort of 221 paediatric patients with mitochondrial disease, the global mortality rate was 14%, with sepsis (55%) and pneumonia (29%) being the two most common causes of death [ 21 ]. Furthermore, there are some animal models, underlying the connection of immunological dysfunction and mitochondrial diseases [ 22 , 23 ]. The presented index patient had a history of recurrent lactic acidosis and ketoacidosis; an immunodeficiency with T cell lymphopenia and hypogammaglobulinemia was suspected.…”
Section: Discussionmentioning
confidence: 99%